WORDLESS PICTURE BOOK: A TEXTBOOK DESIGN FOR JUNIOR HIGH SCHOOL STUDENTS - APRILLIANDARI, DWI INDRA; HANDAYANI, RINDU (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
The research aimed to develop wordless picture book media for junior high school students. The 7th-grade students (Classes A and B) at SMP Muhammadiyah Pangkalpinang were engaged as participants. The four stages of the 4D development processes proposed by S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel are employed in this research and development model: define, design, develop, and disseminate. The data collection techniques included documentation, expert validation, and feasibility test sheets. Two experts contributed to validate the media and the materials. The product feasibility test used the Likert scale to measure teacher's and students’ satisfaction with using the product. The results of questionnaires from media and material experts show that the book is highly valid. The results from the students and teachers of small and large scales were all very good.